Burnout, Anxiety, and Professional Self-Concept in Nurses During the COVID-19 Pandemic in Iran - Alia Saberi; Sajjad Saadat; Ali Pourramazani; Fateme Eftekhari; Hamidreza Hatamian; Marjan Entezari (Acta Medica Iranica, 2022)
The aim of this study was to evaluate the burnout, anxiety, and professional self-concept of nurses according to their demographic and occupational information. 160 nurses from Razi and Poursina hospitals in Iran were selected as a sample in this cross-sectional online survey and answered the tools Demographic and Occupational Information Questionnaire (DOIQ), Maslach Burnout Inventory-Human Services Survey (MBI-HSS), Corona Disease Anxiety Scale (CDAS) and Nurse Self-Concept Questionnaire (NSCQ). Data analysis was performed in two descriptive and inferential sections using SPSS-19 statistics software. The participation rate in this study was 87.5% (n=140). The mean age was 32.56 (SD=7.26) years. The burnout rate in emotional exhaustion (EE) was 24.3%, depersonalization (DP) was 32.1%, and personal accomplishment (PA) was 60.7%, 21.4% of nurses had high anxiety, and 53.6% had low NSCQ. EE score was higher in nurses with less than ten years of experience (t=2.21) and single people (t=-3.18). DP score was higher in people under 35 years (t=3.20), with work experience of fewer than ten years (t=4.34), and single people (t=-3.07). Females in PA reported more burnout (t=-2.43). CDAS score was higher in females (t=3.20). NSCQ score was higher in married people (t=-3.07). CDAS was positively correlated with EE and DP and negatively correlated with PA. NSCQ was negatively correlated with EE and DP and positively correlated with PA. At first, a high CDAS score and then celibacy, less than ten years of work experience, and a low NSCQ score were effective in multiple linear regression analysis for MBI-HSS.